Erratum: Correction: Photoluminescence Modification of Europium(Iii)-Doped Mal2o4 (M = Zn, Mg) Spinels Induced by Ag@Sio2 Core-Shell Nanoparticles (Nanoscale 2024 16 27 Doi: 10.1039/D4nr01526f) - Melo-Hurtado, F (2024)
Correction for Photoluminescence modification of europium(iii)-doped MAl2O4 (M = Zn, Mg) spinels induced by Ag@SiO2 core-shell nanoparticles by Rodrigo A. Valenzuela-Fernandez et al., Nanoscale, 2024, https://doi.org/10.1039/d4nr01526f.